Potential Use of Clove Oil Diluted in VCO On Contaminated Wound Healing - Primandaru, Nibras Wiyasa; Maulana, Andi Muh.; Romdhoni, Muhammad Fadhol; Riyanto, Refni (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2023)
Essential oils, including clove oil, has been used broadly through human civilization due to its multiple benefits, including its utilization as natural antiseptics. In spite of its benefits, clove oil can cause irritation if applied neat to the skin, thus a carrier oil is needed for topical application of clove oil. Clove oil together with virgin coconut oil as a carrier, has potential synergic benefit if applied on contaminated wounds due to its enhanced antiseptic and anti-inflammatory properties. The aim of this study is to investigate the effect of topical application of clove (Syzygium aromaticum) oil diluted in Virgin Coconut Oil on contaminated wound. This study was a quasi-experimental research with post-test only control group design. Clove oil that had been diluted in VCO was applied on contaminated excisional wound in white male rat wistar strain once daily. The wound was inflicted using unsterilized scalpel. The wound was then left exposed to the environment without any dressing and the healing process was then evaluated by measuring the wound area percentage once every four days for sixteen days. Friedman analysis used in this study showed a significant result (p<0,001) and Concentration of 5% clove oil diluted in VCO was found to be the most effective concentration based on the measurement of wound area percentage on the last day of measurement. This study concludes that the topical application of clove oil diluted in VCO showed a significant difference in wound healing process.